Comparative Analysis of Shūshtari Expressional Constructions in Goldberg’s and Filmore’s Grammatical Models - Imaneh Sayad; Sepideh Abdolkarimi (مطالعات زبانی و بلاغی)
Studying Iranian languages and dialects is an undeniable necessity as they are among the most valuable intangible heritage of the country. Besides, the application of recent linguistic theories within theoretical frameworks, which have been less employed as the basis for dialect research is essential since it updates research on dialect and renews the scientific look at languages and dialects. In response to these needs, the present study is an attempt to analyze and compare expressional constructions in Shūshtari dialect based on Goldberg's construction grammar (1995 and 2006) and Fillmore’s et al. (1988) formal-substantive constructions. This research seeks to find out the constructions (fixed or semi-fixed) in Goldberg's classification that correspond to the constructions (formal/substantive) in the Fillmore’s classification. Goldberg's grouping is expected to correspond to Fillmore's division, but the observed mismatch has become the basis for the formation of this study. The data were collected using field and library methods; linguistic data were collected from native speakers of Shūshtari dialect and Glossary of Shūshtari Dialect (Niwand, 1977 and Dictionary of Shūshtari Dialect (Fazeli: 2004). In this research, the expressional constructions of Shūshtari dialect are described and analyzed based on Goldberg’s classification (1995 and 2006) and Fillmore’s et al. (1988) formal-substantive constructions. In the following, an analytical comparison of Goldberg's constructions (fixed or semi-fixed) with Fillmore's (formal/substantive) is presented to correspond between construction groupings to aggregate the categories and achieve a new grouping. The examination of Shūshtari expressions has shown that it is not necessarily possible to correspond the above-mentioned items because, in some cases, semi-fixed constructions correspond to the substantive ones. These observations will be argued in the present study, and ultimately Shūshtar expressional constructions will be regrouped according to Goldberg and Fillmore's divisions. The results of this study can be used in compiling the grammar of Iranian languages and also in teaching them, as well as writing bilingual dictionaries for dialects and also compiling modern Shūshtari dictionary of expressions.